Sources of light - Spilsbury, Louise; Spilsbury, Richard (Chicago, Illinois Heinemann Raintree, 2016)
This book looks at the different places light comes from, including natural and artificial sources. - Discover the difference between a light source and a reflective object and how you can tell which is which. - Look at our largest and most important light source - the Sun - and what happens when you take sunlight away. - Explore light technology by finding out how we use lasers and fiber optics. And much more!"--
A gift from book Africa
Science
1 2 13 15
Keywords: Light sources -- Juvenile literature; Light sources